DESAIN JALUR EVAKUASI PENGGUNA BANGUNAN PADA KONDISI DARURAT DI GEDUNG FTI- UMI LANTAI IV MENGGUNAKAN ALGORITMA FLOYD WARSHALL - Yan Herdianzah; Ahmad Padhil; A. Dwi Wahyuni P; Andi Pawennari; Takdir Alisayabana; Abdul Mail; Taufik Alimuddin; Sadiq Ardo Wibowo (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
It is often assumed that occupational safety and health (K3) is a waste, a waste of cost or just a formality that must be fulfilled by the organization. The K3 procedure in a building is very important especially in a multi-storey building, because in a multi-storey building there are risks that cannot be predicted, for example in the event of an earthquake or fire. Based on the legal aspects of OSH which have been stipulated in Law No. 28 of 2002 concerning building construction, the importance of comfort, safety, health and convenience must be owned by a building. This research is about the evacuation route in the Faculty of Industrial Technology Building, Muslim University of Indonesia, Floor IV Using the Floyd Warshal Algorithm. By using the required data such as building plans, room data used per floor, the number of permanent and temporary building occupants, the results of data processing are obtained from the design drawings of the evacuation route, complete with instructions for safe lane during emergencies.